Chapter 9 Continuums of Violence - Yadav, Punam (Taylor & Francis, 2021)
"This handbook provides a comprehensive overview of feminist approaches to questions of violence, justice, and peace. The volume argues that critical feminist thinking is necessary to analyse core peace and conflict issues and is fundamental to thinking about solutions to global problems and promoting peaceful conflict transformation. Contributions to the volume consider questions at the intersection of feminism, gender, peace, justice, and violence through interdisciplinary perspectives. The handbook engages with multiple feminisms, diverse policy concerns, and works with diverse theoretical and methodological contributions. The volume covers the gendered nature of five major themes: • Methodologies and genealogies (including theories, concepts, histories, methodologies) • Politics, power, and violence (including the ways in which violence is created, maintained, and reproduced, and the gendered dynamics of its instantiations) • Institutional and societal interventions to promote peace (including those by national, regional, and international organisations, and civil society or informal groups/bodies) • Bodies, sexualities, and health (including sexual health, biopolitics, sexual orientation) • Global inequalities (including climate change, aid, global political economy). This handbook will be of great interest to students of peace and conflict studies, security studies, feminist studies, gender studies, international relations, and politics."